2013
DOI: 10.5901/mjss.2013.v4n14p657
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Culture and Religion, Ethnicity, Politics and Poverty on Ethnic Violence in Plateau State of Nigeria

Abstract: Every ethnic nationality has got its own culture and cultural attributes by which the ethnic nationality is known and identified. The inter-play of these cultural attributes as religion or belief system, norms or rules of behaviour, language, history and artefacts, etc. gives rise to politics and determine the nature of the political process in the society, and also the level of pauperization of the people. This paper examines the concepts poverty, culture, politics, religion and ethnicity and how they have fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Again, Siyan et al (2016) empirically studied the implication of unemployment on the poverty level in Nigeria for 1980 to 2104 with the use of VEC for short-run analysis, Johansen co-integration technique and Granger causality with thus revealed the existence of long-run positive relationship between poverty and unemployment and bi-directional Granger causality between poverty and unemployment. Akwara et al (2013) examine the relationship between unemployment, poverty, and insecurity in Nigeria. The study thus discovered that unemployment causes poverty, while poverty causes insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…Again, Siyan et al (2016) empirically studied the implication of unemployment on the poverty level in Nigeria for 1980 to 2104 with the use of VEC for short-run analysis, Johansen co-integration technique and Granger causality with thus revealed the existence of long-run positive relationship between poverty and unemployment and bi-directional Granger causality between poverty and unemployment. Akwara et al (2013) examine the relationship between unemployment, poverty, and insecurity in Nigeria. The study thus discovered that unemployment causes poverty, while poverty causes insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that population pressure and density negatively impact rural poverty (Wang et al, 2018). Furthermore, the extant literature indicates that unemployment ramps up poverty and inequality and negatively influences laid-off individuals and their families and communities (Akwara et al, 2013). Education expenditure and electricity services could reduce national poverty effectively and promote long-term economic development (Jung & Thorbecke, 2003; Ogun, 2010).…”
Section: Data and Modelsmentioning
confidence: 99%
“…Furthermore, they often have low self-esteem, difficulty determining their destiny, and face discriminatory treatment. Akwara et al (2013) argued that absolute poverty is the inability of a person or group to provide the necessities of life and the protection of human dignity. These necessities include food, clothing, shelter, water, health services, primary education, transportation, and work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another concept is relative poverty. According to Akwara et al (2013), specific societal sectors cannot meet their basic needs. This occurs due to the inability of the community to achieve a minimum standard of living in their area.…”
Section: Literature Reviewmentioning
confidence: 99%